THE EFFECT OF GRAPHIC MEDIA ON STUDENTS’ WRITING EXPLANATION TEXT ABILITY AT X GRADE STUDENTS OF YPP BAITUR RAHMAN 2018/2019 ACADEMIC YEAR - Nuraisyah Nasution (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstrak: The objective of this research is to know whether there is a significant effect of using graphic media on Students’ Writing Explanation Text Ability at Tenth Grade Students of YPP Baitur Rahman. Method of this research is experimental method with the experimental research design; one group pre-test and post-test design. The population are all of the tenth grade students which consist of 65 students. Technique sampling that used on this research is purposive sampling and the number of the sample consists of 28 students. In collecting the data, the writer uses observation sheet to get the data of the application of graphic media and test to get the data of students’ writing explanation text. writer uses statistic process in analyzing by using t test formula. Based on the data that has been analyzed, the result of analyzed data showed that t test is higher than t table (t test 17.79 > t table 2.05), and the hypothesis is accepted. It means that there is a significant effect of graphic media on Students’ Writing Explanation Text Ability at Tenth Grade Students of YPP Baitur Rahman.